Editorial: Biomolecular Technology of Proteins – BioToP. Issue 4 (April 2014) - Obinger, Christian
<x xml:space="preserve">Abstract</x> Current doctoral students who will be the driving force of science in the future. Christian Obinger, speaker of the BioToP Phd program "Biomolecular Technology of Proteins – BioToP", reviews the articles in this BioToP Special issue. <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>